Spring Awakening. - Wedekind, Frank (Menthuen Drama, 2009)
Set in late 19th century Germany, it concerns teenagers who are discovering the inner and outer tumult of sexuality. The plays performance was threatened with closure when the city's Commissioner of Licenses claimed that the play was pornographic, due to its portrayal of abortion, homosexuality, rape, child abuse, and suicide, but a New York trial court issued an injunction to allow the production to proceed.